2020
DOI: 10.3389/fonc.2020.00780
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Validation of a Prognostic lncRNA Signature for Hepatocellular Carcinoma

Abstract: Background: An accumulating body of evidence suggests that long non-coding RNAs (lncRNAs) can serve as potential cancer prognostic factors. However, the utility of lncRNA combinations in estimating overall survival (OS) for hepatocellular carcinoma (HCC) remains to be elucidated. This study aimed to construct a powerful lncRNA signature related to the OS for HCC to enhance prognostic accuracy. Methods: The expression patterns of lncRNAs and related clinical data of 371 HCC patients were obtained based on The C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 32 publications
2
46
0
Order By: Relevance
“…Evidence has recently indicated that lncRNAs can regulate immune cell differentiation and function, such as dendritic cell activity, T cell ratio, and metabolism (6), and thus, are potential targets for cancer therapeutics and possess predictive value for survival prognosis (4). Through mining the transcriptome sequencing data via the bioinformatics analysis, many studies have already established the lncRNA signature for predicting the prognosis of cancers, including thyroid cancer (19), breast cancer (20), renal cell carcinoma (21), bladder cancer ( 22), gastric cancer (23), as well as HCC (24). In this study, we aimed to construct an immune-related lncRNAs signature in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has recently indicated that lncRNAs can regulate immune cell differentiation and function, such as dendritic cell activity, T cell ratio, and metabolism (6), and thus, are potential targets for cancer therapeutics and possess predictive value for survival prognosis (4). Through mining the transcriptome sequencing data via the bioinformatics analysis, many studies have already established the lncRNA signature for predicting the prognosis of cancers, including thyroid cancer (19), breast cancer (20), renal cell carcinoma (21), bladder cancer ( 22), gastric cancer (23), as well as HCC (24). In this study, we aimed to construct an immune-related lncRNAs signature in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Several lncRNA-based prognostic models have been used for many malignancies, such as carcinoma of lung, bladder and breast(26-30), etc. Several researches have constructed lncRNA-based risk models of HCC, but the existing risk models mostly based on the overall survival rather than disease free survival (31)(32)(33)(34). In this study, we screened both DFS-associated and OSassociated DElncRNAs in the TCGA databases by univariate Cox and LASSO regression, then established two lncRNA-based signatures focusing on DFS and OS respectively, both of the prognostic models were validated and showed good performance.…”
Section: Discussionmentioning
confidence: 99%
“…The present study focused on identifying miRNAs related to VI in HCC. Unlike other database-based studies [41][42][43], all the study subjects were HCC patients, to more accurately screen for differentially expressed miRNAs related to VI. Patients who met the inclusion criteria were divided into two groups based on whether or not they had VI, and the differences in miRNA expression levels analyzed.…”
Section: Discussionmentioning
confidence: 99%